2000
DOI: 10.3171/spi.2000.93.2.0199
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of kyphotic deformity following laminectomy for cervical spondylotic myelopathy

Abstract: Object. The authors undertook a study to explore the predisposing risk factors, frequency of occurrence, and clinical implications of kyphosis following laminectomy for cervical spondylotic myelopathy (CSM). Methods. Preoperative radiological studies were available in 46 patients with CSM who had undergone laminectomy. Records were reviewed to obtain demographic data and operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
179
2
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(196 citation statements)
references
References 45 publications
(49 reference statements)
5
179
2
7
Order By: Relevance
“…There was consensus in the literature that preoperative severity (n = 2) was not significantly associated with postoperative radiculopathy. 24,65 Risk factors for stability complications such as instability (n = 1) 25 and postoperative kyphosis (n = 2) 35,64 were assessed by 3 studies. Guigui et al reported that patients who were younger (p = 0.03), had a hypermobile spine (p < 0.0001), had greater preoperative range of motion (p < 0.0001), and received a C-2 laminectomy (p = 0.0164) were more susceptible to spinal destabilization.…”
Section: 42mentioning
confidence: 99%
“…There was consensus in the literature that preoperative severity (n = 2) was not significantly associated with postoperative radiculopathy. 24,65 Risk factors for stability complications such as instability (n = 1) 25 and postoperative kyphosis (n = 2) 35,64 were assessed by 3 studies. Guigui et al reported that patients who were younger (p = 0.03), had a hypermobile spine (p < 0.0001), had greater preoperative range of motion (p < 0.0001), and received a C-2 laminectomy (p = 0.0164) were more susceptible to spinal destabilization.…”
Section: 42mentioning
confidence: 99%
“…Although progressive cervical kyphosis after cervical laminectomy has been associated with myelopathy, postlaminectomy kyphotic deformity is not clearly related to the postoperative clinical outcome. 11 Moreover, patients with cervical kyphosis, as well as patients whose postoperative cervical alignment changes from lordotic to straight, often have poor surgical outcomes after laminoplasty. 7 Due to these concerns, a variety of laminoplasty techniques have been developed to decrease postoperative kyphotic deformity.…”
mentioning
confidence: 99%
“…The complications of decompression surgeries for cervical spondylotic myelopathy have been widely discussed, including approach relevant lesions [17,18], decompression relevant nerve lesions [19,20], fusion relevant adjacent segment disease [21] and others [22][23][24]. Migration of spinal cord is one of the complications of decompression surgical procedure which has been reported for years [10][11][12].…”
Section: Discussionmentioning
confidence: 99%